Do people care about context? Framing effects in dictator games - Anna Dreber; Tore Ellingsen; Magnus Johannesson; David G. Rand (Stockholm School of Economics, The Economic Research Institute (EFI), 2011)
Many previous experiments document that behavior in multi-person settings responds to the name of the game and the labeling of strategies. Usually these studies cannot tell whether frames affect preferences or beliefs. In this Dictator game study, we investigate whether social framing effects are also present when only one of the subjects makes a decision, in which case the frame may only affect preferences. We find that behavior is insensitive to social framing.
Keywords: C70; C91; D03; D64; 330; beliefs; preferences; framing effects; altruism; cooperation; Verhalten; Spieltheorie; Framing; Altruismus; Test